PC coach athletic training software (Broadway : PC Coach, 1999)
PC coach with SonicLink and the Polar coach with monitor comprise the most advanced and fully integrated system of athletic training available
Systems requirements: CD-ROM drive, sound card, microphone, 486 or better, Windows 95 or better, hard disk: 10 MB RAM free, memory 16 MB RAM, video VGA or better
Keywords: Athletics -- Computer programs; Athletics -- Computer-assisted instruction